MEMBANGUN KEUNGGULAN KOMPETITIF MELALUI ALIANSI STRATEJIK UNTUK MENINGKATKAN KINERJA PERUSAHAAN (Studi Kasus Pada PT. Pos Indonesia Wilayah VI Jateng dan DIY) - Prasetya, Hery (PRESTASI, 2009)
This research head for analyse the effect of inter variable to answered set problems how is innovation product, strategic alliance and the change of environment create competitive advantage to improve company performance. This research gives teoritic implication along with managerial implication concern pace wich have to take by PT. Pos Indonesia to improve their company performance pass through competitive advantage which got from product innovation, strategic alliance and change of environment.Population in this research is post office in Zone VI Central Java and DIY has on-line. From 272 quesionair has spread, come back 111. Answer data from respondent afterwards itâs analysed with research model which developed from teoritic frame using analysis confirmatory SEM. From result of analyse data seen from six hypotesis just four which accepted. Change of environment proven has an positively effect for strategic alliance and competitive advantage, strategic alliance have an positive effect for competitive advantage and competitive advantage have an positive effect for company performance. Innovation product proved doesnât have effect to strategic alliance and competitive advantage.Â Key words :Â Â Â Â  Innovation Product, Strategic Alliance, Change of Environment, Competitive Advantage and Company Performance